Political Parties, Supply-Side Strategies, and Firms: The Political Micro-Economy of Partisan Politics. (4th June 2014) - Camyar, Isa
Abstract : This research examines the economic impact of partisan politics at a level that has been neglected in prior research: the firm level. Specifically, I investigate the impact of partisan supply-side policies on firm performance and firm heterogeneity in experience of this impact. I claim that parties' supply-side strategies (the interventionist strategy of left-wing parties and the market-oriented strategy of right-wing parties) have conflicting implications for the productivity and cost of economic factors at the disposal of firms. My empirics employ firm-level data from 21 advanced industrial democracies for the period extending from 1989 to 2008. The results are counterintuitive and, in some ways, even provocative. I find that (1) firms perform better under left-oriented governments compared to right-oriented governments, suggesting that the interventionist strategy of left-wing parties helps firms better than the market-oriented strategy of right-wing parties; and (2) there is considerable firm heterogeneity in exposure to partisan supply-side strategies.